Susceptibility Assessment of Multidrug Resistant Bacteria to Natural Products - Essam Hassan Mohamed; Youssef Saeed Alghamdi; Salama Mostafa Abdel-Hafez; Mohamed Mohamed Soliman; Saad H. Alotaibi; Magdy Yassin Hassan; Nasr Al-Deen Hany; Hamada H. Amer (SAGE Publishing, 2020)
Objective: The aim of this study was to examine the effect of some natural compounds against multidrug-resistant bacteria. Methods: Forty-three bacterial strains were collected. Disc diffusion and minimum inhibitory concentration (MIC) tests were carried out for natural compounds including quercetin, Acacia nilotica , Syzygium aromaticum , and Holothuria atra . Scanning electron microscope analysis and bacterial DNA apoptosis assays were performed. Results: Staphylococcus aureus strains were resistant to imipenim, ampicillin, and penicillin. Most Escherichia coli strains were resistant to amoxicillin, clavulanat, and ampicillin. Finally, tigecycline was effective with Klebsiella pneumoniae and was resistant to all antibiotics. Only S aromaticum had an antibacterial effect on K pneumoniae . Most S aureus strains were sensitive to S aromaticum , A nilotica , and quercetin. All examined natural extracts had no effect on E coli . Holothuria atra had no effect on any of the strains tested. Minimum inhibitory concentration and minimum bactericidal concentration values for examined plants against S aureus were 6.25 to 12, 1.6 to 3.2, and 9.12 to 18.24 mg/mL, respectively. Syzygium aromaticum was active against K pneumoniae with an MIC of 12.5 mg/mL. Scanning electron microscope analysis performed after 24 and 48 hours of incubation showed bacterial strains with distorted shapes and severe cell wall damage. Syzygium aromaticum , quercetin, and A nilotica showed clear fragmentations of S aureus DNA. Conclusions: Current findings confirmed the beneficial effect of using natural products such as clove (S aromaticum) , quercetin, and A nilotica as a promising therapy to overcome multidrug resistant bacteria.